2021
DOI: 10.3390/su13115762
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging COVID-19 Outbreak for Shaping a More Sustainable Consumer Behavior

Abstract: Consumption has lately been under the microscope facing pressure from all stakeholders as principles of sustainability have gained more popularity. In this context, a new sustainable consumer model was born, referring to major shifts in buying and consumption habits. Nevertheless, these shifts were lagging as consumers resisted change in the comfort of old habits. This comfort was shaken up by the COVID-19 outbreak that forced us to rethink every aspect of our lives. Therefore, this crisis context seems the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 47 publications
0
24
0
1
Order By: Relevance
“…The first topic emerging from the analysis concerns organic food consumption, i.e., food that is produced through environmentally friendly agricultural methods, without fertilizers and synthetic chemicals [96]. This result is not surprising given that the concern for health, including healthy eating, is gaining importance among consumers during the COVID-19 pandemic [18,24]. It is confirmed that if consumers are health-conscious, organic food is their first choice [97][98][99].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The first topic emerging from the analysis concerns organic food consumption, i.e., food that is produced through environmentally friendly agricultural methods, without fertilizers and synthetic chemicals [96]. This result is not surprising given that the concern for health, including healthy eating, is gaining importance among consumers during the COVID-19 pandemic [18,24]. It is confirmed that if consumers are health-conscious, organic food is their first choice [97][98][99].…”
Section: Discussionmentioning
confidence: 92%
“…[11][12][13][14][15][16][17]. Although it is impossible to identify all of them, due to the growing interest in health issues during the pandemic, consumer behavior is evolving towards healthier and more sustainable patterns [3,18]. Among these publications, studies on the impact of the pandemic on sustainable consumption have a large share [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the appearance of new sustainable consumers obliged a change in buying and consuming intentions and processes. To reach long-term growth, therefore, companies and consumers should overlook the traditional forms of production and consumption and orientate themselves toward sustainable economies that respecting corporate values, business ethics, and corporate governance to face the current environmental and social challenges [29]. Nowadays, customers are more likely to be influenced and motivated not only by family and friends' perceptions but also by the amount of the shared information or knowledge through social media, including advertisements and other people's experiences, which considerably influence their purchasing behaviors.…”
Section: Cpb and Consumer Knowledge Sharing Behaviormentioning
confidence: 99%
“…Efficient adaptation to shocks, the emergence of change, and embracing it with proper managerial techniques and resilience, which all require coordinated and concentrated efforts to maximize intersectoral synergies and minimize trade-offs [51] as well as proper management of the use of water, energy, land and other crucial resources, does not only encompass an environmental perspective, but an economic perspective as well [52]. This is a major challenge, especially for developing countries, which are still facing issues in achieving food, water, and energy security, which is directly correlated to climate change issues [53,54].…”
Section: Literature Reviewmentioning
confidence: 99%